Synyuk O.M. Experimental research of destruction of polyethylene and polypropylene films - Синюк, О. М. (Problems of Tribology, 2018)
The dependence of the specific energy of formation of the free surface unit of recycled polyethylene and polypropylene films on various values of structural and technological parameters of a roller device was experimentally investigated. The equations obtained from the approximation of the results of the investigation can describe the change in the specific energy of the formation of a free surface unit during the recycling of polypropylene and polyethylene films from the structural and technological parameters of the device with toothed rolls, namely the frequency of rotation of the toothed rolls and the step of the teeth. These dependencies can be used in calculations of technological and structural parameters of equipment for the recycling of polymeric waste from light industry.